2018
DOI: 10.1016/j.asr.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Physics of meteor generated shock waves in the Earth’s atmosphere – A review

Abstract: Shock waves and the associated phenomena generated by strongly ablating meteoroids with sizes greater than a few millimeters in the lower transitional flow regime of the Earth's atmosphere are the least explored aspect of meteor science. In this paper, we present a comprehensive review of literature covering meteor generated shock wave phenomena, from the aspect of both meteor science and hypersonic gas dynamics. The primary emphasis of this review is placed on the mechanisms and dynamics of the meteor shock w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 263 publications
2
98
0
2
Order By: Relevance
“…The consideration of varying γ is best suited for numerical models, although some modeling studies did apply γ = 1.4 and found that the main dependences of the vapour (hydrodynamic shielding) parameters, and consequently the temperature and density jumps, are the size and the altitude of the meteoroid (see Popova et al 2000 and Section 1.2). Also, the consideration of an ablating centimeter-sized meteoroid entering at velocities up to 73 km/s is very different and profoundly more complex than, for example, a much larger re-entry vehicle at significantly lower velocities (e.g., 7 km/s) (see Silber et al 2018b for discussion).…”
Section: Validation Of the Results With Two Knudsen Classification Scmentioning
confidence: 99%
“…The consideration of varying γ is best suited for numerical models, although some modeling studies did apply γ = 1.4 and found that the main dependences of the vapour (hydrodynamic shielding) parameters, and consequently the temperature and density jumps, are the size and the altitude of the meteoroid (see Popova et al 2000 and Section 1.2). Also, the consideration of an ablating centimeter-sized meteoroid entering at velocities up to 73 km/s is very different and profoundly more complex than, for example, a much larger re-entry vehicle at significantly lower velocities (e.g., 7 km/s) (see Silber et al 2018b for discussion).…”
Section: Validation Of the Results With Two Knudsen Classification Scmentioning
confidence: 99%
“…Second, the numerical models best describe the motion and physical and chemical behaviour of hypersonic objects at lower velocities. For a detailed discussion about the challenges in numerically modeling meteoroids, the reader is referred to [Silber et al, 2018b].…”
Section: Methodsmentioning
confidence: 99%
“…However, it should be noted that the actual flow field of a strongly ablating meteoroid at higher velocities is much larger than the characteristic object size (e.g., see [Silber et al, 2018b, Silber et al, 2018a). Consequently, the fragment sizes were chosen to satisfy the flow field requirements corresponding to the continuous flow regime [Silber et al, 2018b].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meteoroids collide with the Earth's atmosphere on a daily basis. On average, meteoroids cumulatively deposit about 5 to 300 tons of material per day (Plane, 2012;Silber, Boslough, Hocking, Gritsevich, & Whitaker, 2018), mostly into our atmosphere and only a tiny amount to the Earth's surface in a form of meteorite falls. Meteors have been an integral part of astronomy since ancient times as they are easily observed with the naked eye.…”
Section: Introductionmentioning
confidence: 99%